Formations theory in soviet school textbooks on general history - Elena A. Pevtsova, Vardan E. Bagdasaryan; Novoselova, Svetlana Yu.; Potemkina, Tatiana V.; Kurnosova, Svetlana A.; Malevanov, Evgeniy Yu. (Opción, 2020)
The purpose of the article is to analyze the Soviet experience of representing the world’s historical process in the framework of the theory of changing social formations via the content analysis of Soviet school textbooks in relation to the formations-based structuring of history. As a result, the idea of a proletarian revolution was, according to the authors of textbooks, replaced by a bet on petty- bourgeois forces. In conclusion, in the USSR it was possible to create an integral model of systematic historical education in schools that allows solving current ideological problems.